Toxic‐Free Aqueous Gelcasting of Alumina Ceramics Using Alumina Sol Binder. (19th November 2014) - Manivannan, Ramalingam; Kumar, Anil; Jain, Rajnish Kumar; Subrahmanyam, Challapalli
Abstract : An eco‐friendly gelcasting system has been developed for the fabrication of alumina ceramics using alumina sol as a binder. 0.5 wt% of ammonium polymethacrylate dispersant was used based on total alumina solid loading to obtain completely dispersed slurry with high solid loading. Ceramic slurries having different volume percentage of alumina loading from 46 to 52 vol% in alumina sol were made, and the rheological properties were evaluated. 51 vol% of alumina slurry having viscosity 0.73 Pa.s with 2 wt% of alumina sol binder content per weight of alumina was optimized. The gelling behavior of concentrated slurry was evaluated by measuring storage modulus, and the consolidated green sample is homogeneous and exhibiting the bending strength of 4 MPa and 55% theoretical density. On sintering the sample at 1550°C for 2 h, the flexural strength was found to be 317 ± 30 MPa, and the corresponding theoretical density was 98%.